The Differences between Male and Female Pupils in Accessing Porn - Indraswari, Ratih; Kusumawati, Aditya; Handayani, Novia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Children have begun to be exposed to pornography at a very young age, which is 4 years. Intentionally or not, access to pornography has a brain-damaging impact. Pornography damages the human brain worse than drugs. Objective: This study aims to identify behavioral differences in pornography consumption in male and female pupils aged 9-11 years. Method: The research data were obtained by using a survey method for 261 pupils aged 9-11 years who attend public elementary schools in Semarang city. The data were analyzed univariate and bivariate to determine behavioral differences between male and female pupils. Results: There are 53.3% of female and 46.7% of male pupils participated in this study. Most of them are 11 years old (62.8%) and not yet pubescent (79.7%). As much as 30.7% of pupils (16.1% male and 14.6% female) have accessed pornography and 15.4% accessed it intentionally. Almost 7% of pupils access pornography more than 1 minute, by cellular phone (27.6%) and 5.4% frequently access it for more than 5 times a week. There are no significant differences between male and female students in pornography consumption (p=0.095). The government through Health Office should cooperate with schools and families in making educational programs about the dangers of pornography. Parents should control the use of the cellular phone by children. Due to no behavioral difference in pornography consumption, the intervention program provided could be in equal portions between female and male pupils.